Prostaglandin F(2α)-F-prostanoid receptor regulates CXCL8 expression in endometrial adenocarcinoma cells via the calcium–calcineurin–NFAT pathway - Sales, Kurt J. (Elsevier Pub. Co, 2009)
Pro-inflammatory mediators, like prostaglandin (PG) and chemokines, promote tumourigenesis by enhancing cell proliferation, migration of immune cells and recruitment of blood vessels. Recently we showed elevated expression of the chemokine (C-X-C motif) receptor 2 (CXCR2) in endometrial adenocarcinomas localized to neutrophils and neoplastic epithelial and vascular cells. Furthermore we found that PGF(2α)-F-prostanoid (FP) receptor regulates the expression of the CXCR2 ligand CXCL1, to promote neutrophil chemotaxis in endometrial adenocarcinomas. In the present study we identified another CXCR2 ligand, CXCL8 as a target for PGF(2α)-FP receptor signalling which enhances epithelial cell proliferation in endometrial adenocarcinoma cells in vitro and in nude mice in vivo. We found that PGF(2α)-FP receptor interaction induces CXCL8 expression in endometrial adenocarcinoma cells via the protein kinase C–calcium–calcineurin–NFAT signaling pathway. Promoter analysis revealed that CXCL8 transcriptional activation by PGF(2α) signaling is mediated by cooperative interactions between the AP1 and NFAT binding sites. Furthermore, PGF(2α) via the FP receptor induced the expression of the regulator of calcineurin 1 isoform 4 (RCAN1-4) via the calcineurin/NFAT pathway in a reciprocal manner to CXCL8. Using an adenovirus to overexpress RCAN1-4, we found that RCAN1-4 is a negative regulator of CXCL8 expression in endometrial adenocarcinoma cells. Taken together our data have elucidated the molecular and cellular mechanism whereby PGF(2α) regulates CXCL8 expression via the FP receptor in endometrial adenocarcinomas and have highlighted RCAN1-4 as a negative regulator of CXCL8 expression which may be exploited therapeutically to inhibit CXCL8-mediated tumour development.